P732 The clinical efficacy and safety of indigo naturalis in induction & maintenance therapy for moderate-to-severe ulcerative colitis: A single-centre prospective uncontrolled open-label study. (15th January 2020) - Matsuno, Y; Hirano, A; Torisu, T; Fuyuno, Y; Okamoto, Y; Shin, F; Tomohiko, M; Umeno, J; Hirakawa, Y; Esaki, M; Kitazono, T
Abstract: Background: Recently, several studies have shown the high efficacy of Indigo naturalis (IN) in the induction therapy for ulcerative colitis (UC). However, the efficacy and safety in the maintenance therapy remain unclear. Thus, we performed this prospective study to investigate the efficacy and safety of IN for induction and maintenance therapy in patients with moderate to severe active UC. Methods: We conducted a prospective uncontrolled open-label study at Kyushu university hospital. A total of 33 patients with moderate to severe active UC (clinical activity index (CAI) ≥8) received 2 g per day of IN for 52 weeks. We assessed CAI at week 0, 4, 8, 52, and Mayo endoscopic score (MES) was evaluated at weeks 0, 4, 52. We calculated the clinical remission (CAI ≤4) rate and mucosal healing (MES ≤1) rate at each point. Overall adverse events (AEs) during the follow-up were also estimated. Results: Clinical remission rates at weeks 4, 8, and 52 were 67%, 76%, and 73%, respectively. Mucosal healing rates at weeks 4 and 52 were 48% and 70%. Seventeen patients experienced adverse events (AEs) during the follow-up. Seven severe AEs, including intussusceptions, acute severe colitis, infectious colitis, portal thrombosis, appendicitis, were observed in 4 patients. Conclusion: Our prospective study indicated that IN was a promising option for induction and maintenance therapy in UC. However, possible AEs of IN should be paid attention.